Influence of socio-economic and lifestyle factors on overweight and nutrition-related diseases among Tunisian migrants versus non-migrant Tunisians and French - Delpeuch Francis; El Ati Jalila; Eymard-Duvernay Sabrina; Traissac Pierre; Méjean Caroline; Maire Bernard (BMC, 2007)
Abstract Background Migrant studies in France revealed that Mediterranean migrant men have lower mortality and morbidity than local-born populations for non-communicable diseases (NCDs). We studied overweight and NCDs among Tunisian migrants compared to the population of the host country and to the population of their country of origin. We also studied the potential influence of socio-economic and lifestyle factors on differential health status. Methods A retrospective cohort study was conducted to compare Tunisian migrant men with two non-migrant male groups: local-born French and Tunisians living in Tunisia, using frequency matching. We performed quota sampling (n = 147) based on age and place of residence. We used embedded logistic regression models to test socio-economic and lifestyle factors as potential mediators for the effect of migration on overweight, hypertension and reported morbidity (hypercholesterolemia, type-2 diabetes, cardiovascular diseases (CVD)). Results Migrants were less overweight than French (OR = 0.53 [0.33-0.84]) and had less diabetes and CVD than Tunisians (0.18 [0.06-0.54] and 0.25 [0.07-0.88]). Prevalence of hypertension (grade-1 and -2) and prevalence of hypercholesterolemia were significantly lower among migrants than among French (respectively 0.06 [0.03-0.14]; 0.04 [0.01-0.15]; 0.11 [0.04-0.34]) and Tunisians (respectively OR = 0.07 [0.03-0.18]; OR = 0.06 [0.02-0.20]; OR = 0.23 [0.08-0.63]). The effect of migration on overweight was mediated by alcohol consumption. Healthcare utilisation, smoking and physical activity were mediators for the effect of migration on diabetes. The effect of migration on CVD was mediated by healthcare utilisation and energy intake. No obvious mediating effect was found for hypertension and hypercholesterolemia. Conclusion Our study clearly shows that lifestyle (smoking) and cultural background (alcohol) are involved in the observed protective effect of migration.